Beyond the balanced scorecard : improving business intelligence with analytics - Brown, Mark Graham (New York : Productivity Press, 2007)
This book provides managers with the right metrics for evaluating important aspects of performance that are not accurately tracked by most companies and government organizations.
Includes bibliographical references and index.
Loans
Keywords: Organizational effectiveness -- Evaluation; Performance -- Management; Business intelligence; Business mathematics